Obesity and Oesophageal Adenocarcinoma: Underlying Mechanisms : Case Study - Fairhurst, Natalie; Owen, Richard (Journal of the Nuffield Department of Surgical Sciences, 2020)
The incidence of oesophageal adenocarcinoma (OA) in the Western World has drastically increased by almost 400% in the last 30 years, making it the 8th most common cancer in the World. This cancer normally presents in late-stage disease meaning that therapeutic options are limited. Given this, identification of modifiable predisposing factors is crucial in order that therapeutic intervention can be targeted correctly. In the present case report, we describe the case of a 59 year-old woman diagnosed with T2 oesophageal adenocarcinoma on a background of BMI 49 and few other predisposing co-morbidities. This case highlights the difficulty in identfying causal relationships between obesity and oesophageal adnocarcinoma, and the limitations this brings to managing cases in practice. Further evidence is needed to define the pathophysiology of the disease as well as potential predisposing factors which can be targeted therapeutically to mitigate against disease development and progression.